Vir inversus - Männlichkeiten im spanischen Schelmenroman - Schuhen, Gregor (Lettre, 2018)
Picaresque novels are violent, satirical and usually dominated by males. Gregor Schuhen illuminates this combination from the viewpoint of masculinity studies and explores specifically male practices and ideals